Technological behaviour in the early Acheulean of EF-HR (Olduvai Gorge, Tanzania). Issue 120 (July 2018) - de la Torre, Ignacio; Mora, Rafael
Abstract: Technological strategies of early humans are discussed in the light of a recently excavated stone tool assemblage from EF-HR, an archaeological site older than 1.33 Ma at Olduvai Gorge, Tanzania. Renewed fieldwork at EF-HR has unearthed a lithic collection containing over 2300 artefacts (including a hundred handaxes in stratigraphic position), which represents one of the largest assemblages for the early Acheulean in eastern Africa. Our technological study shows co-occurrence of two distinctive reduction sequences in the same assemblage, one aimed at obtaining small flakes and the other focused on the production of large, thick, heavy flakes that were then used as blanks for handaxe shaping. Flaking of small cores is expedient and low intensity, and knapping methods are similar to those observed in earlier Oldowan assemblages. Large Cutting Tools (LCTs) show no evidence of planform and biconvex symmetry, and shaping sequences are brief and discontinuous, indicating short use-lives for handaxes. Bifaces are rare and atypical. Recurrent morphotypes are knives, which are poorly-shaped, scraper-like, large-sized handaxes. Despite the apparent expediency of EF-HR handaxe production, a closer inspection of the interplay between debitage and façonnage stages reveals remarkably standardized procedural patterns. Large Cutting Tool blanks were produced following fixed knapping rules resulting in flakes with a specific morphology and mass distribution. Adapted to the idiosyncrasies of each blank, shaping was almost invariably imposed over the same areas in all LCTs and sought to produce morphotypes that, technologically, are remarkably identical to each other. This strongly supports the existence of mental templates and technical rules that were systematically practiced in LCT production at EF-HR, and underscore the structured nature of technological behaviour at the onset of the Acheulean in eastern Africa.